DNMT3A transcriptionally downregulated by KLF5 alleviates LPS-induced inflammatory response and promotes osteogenic differentiation in hPDLSCs - Jianling GUO; Huijie JIA (University of São Paulo, 2024)
Abstract Background and objective Periodontitis is an inflammatory disease typically characterized by the destruction of periodontal tissues and complicated etiology. DNA methyltransferase 3A (DNMT3A) has been implicated in possessing pro-inflammatory properties. This study sought to explore the role of DNMT3A in periodontitis and its relevant mechanism. Methodology Lipopolysaccharide (LPS) was used to induce inflammation in human periodontal ligament stem cells (hPDLSCs). DNMT3A and KLF5 expressions were detected using RT-qPCR and western blot. The levels of inflammatory cytokines and inflammation-related proteins were detected using ELISA and western blot. NF-κB p65 expression was detected using immunofluorescence (IF) assay, while osteogenic differentiation was assessed using ALP assay and ARS staining. Western blot was used to measure the protein contents associated with osteogenic differentiation. DNMT3A activity was detected using luciferase report assay and chromatin immunoprecipitation (ChIP) was used to verify the interaction between KLF5 and DNMT3A. Results DNMT3A expression increased in LPS-induced hPDLSCs. Silencing DNMT3A suppressed the LPS-induced inflammation in hPDLSCs, while promoting osteogenic differentiation. It was also found that transcriptional factor KLF5 could bind to DNMT3A promoters and regulate DNMT3A expression. Rescue experiments showed that KLF5 interference partially counteracted the inhibitory impacts of DNMT3A deficiency on inflammation and the promotive effects on osteogenic differentiation in LPS-induced hPDLSCs. Conclusion DNMT3A, when transcriptionally downregulated by KLF5, could alleviate LPS-challenged inflammatory responses and facilitate osteogenic differentiation in hPDLSCs.